Multimodal pattern recognition of social signals in human-computer-interaction : 5th IAPR TC 9 Workshop, MPRSS 2018, Beijing, China, August 20, 2018, Revised selected papers /: 5th IAPR TC 9 Workshop, MPRSS 2018, Beijing, China, August 20, 2018, Revised selected papers. ([2019]) - Unknown
No abstract available